POST MORTEM CASE REPORT OF A KALAHARI RED DOE THAT DIED OF COMPLICATIONS OF MULTIFACTORIAL DYSTOCIA - MUSHONGA, B; CHIWOME, B; KANDIWA, E; HABARUGIRA, G; SAMKANGE, A (The Indian Journal of Animal Reproduction, 2017)
A triparous Kalahari Red doe was presented for post-mortem with a sero-sanguinous vulvular discharge and abdominal distension. At necropsy, two foetuses, male and female, about 3.5 kg each were observed. The left lateral abdominal muscles of the doe presented with a tear that corresponded with another tear on the lateral aspect of the left horn of the uterus and showing a partial protrusion of the cranium of a male twin. The male twin was lodged in an incompletely dilated cervix in a caudal longitudinal presentation, dorso-sacral position, and bilateral hip flexion posture. The same twin also presented with a left lateral abdominal wall rupture and herniation of the urinary bladder and intestines. The female twin was in the right uterine horn in a cranial longitudinal presentation, dorso-sacral position, but with bilateral carpal flexure. In brief, the circulatory collapse due to a multifactorial dystocia was the final diagnosis.